A Pilot Investigation of Nonpharmacological Pain Management Intervention Groups in Methadone Maintenance Treatment. Issue 2 (17th March 2022) - DiMeola, Kimberly A.; Haynes, Jeff; Barone, Meredith; Beitel, Mark; Madden, Lynn M.; Cutter, Christopher J.; Raso, Anthony; Gaeta, Marina; Zheng, Xiaoying; Barry, Declan T.
Abstract : Objectives: We examined the feasibility (i.e., single-session attendance) of conducting 3 counselor-delivered nonpharmacological pain management intervention (NPMI) groups in methadone maintenance treatment (MMT): (1) Coping with Pain, an intervention based on cognitive-behavioral therapy, (2) Wii-Covery, an exergame intervention to facilitate exercise, and (3) Juggling Group, an intervention to promote social inclusion and reduce stress. We examined pre-post session changes in pain and mood associated with group attendance. Methods: Over 1 month at an MMT clinic with 1800 patients, each NPMI group was offered daily Monday-Friday and 1 was offered on Saturdays. A standardized but unvalidated measure was administered before and after sessions to assess acute changes in current pain intensity and mood states. Paired t -tests with Bonferroni corrections were performed for each NPMI group ( P < 0.0007 [.05/7]). Results: About 452 patients (67% male, 84% White, mean age, 40) attended at least 1 NPMI group. About 57% reported current chronic pain. Attendance at any NPMI group (for the whole sample and the subset with chronic pain) was significantly associated with acute reductions in current pain intensity, anxiety, depression, and stress, and acute increases in current energy and happiness. Attendance at Coping with Pain and Juggling Group was also associated with acute increases in compassion. Conclusions: Coping with Pain, Wii-Covery, and Juggling Group are feasible to conduct in MMT, and acute improvements in current pain intensity and specific mood states associated with a single session attendance point to the importance of examining systematically the efficacy of these and other NPMIs in MMT.